Mycobacterial mutants with defective control of phagosomal acidification. - Graham R Stewart; Janisha Patel; Brian D Robertson; Aaron Rae; Douglas B Young (PLoS Pathogens)
The pathogenesis of mycobacterial infection is associated with an ability to interfere with maturation of the phagosomal compartment after ingestion by macrophages. Identification of the mycobacterial components that contribute to this phenomenon will allow rational design of novel approaches to the treatment and prevention of tuberculosis. Microarray-based screening of a transposon library was used to identify mutations that influence the fate of Mycobacterium bovis bacille Calmette-Guérin (BCG) following uptake by macrophages. A screen based on bacterial survival during a 3-d infection highlighted genes previously implicated in growth of Mycobacterium tuberculosis in macrophages and in mice, together with a number of other virulence genes including a locus encoding virulence-associated membrane proteins and a series of transporter molecules. A second screen based on separation of acidified and non-acidified phagosomes by flow cytometry identified genes involved in mycobacterial control of early acidification. This included the KefB potassium/proton antiport. Mutants unable to control early acidification were significantly attenuated for growth during 6-d infections of macrophages. Early acidification of the phagosome is associated with reduced survival of BCG in macrophages. A strong correlation exists between genes required for intracellular survival of BCG and those required for growth of M. tuberculosis in mice. In contrast, very little correlation exists between genes required for intracellular survival of BCG and those that are up-regulated during intracellular adaptation of M. tuberculosis. This study has identified targets for interventions to promote immune clearance of tuberculosis infection. The screening technologies demonstrated in this study will be useful to the study of pathogenesis in many other intracellular microorganisms.